Identifying Spillover Effect & Bubble in Bangladeshi Asset Markets: An Analysis of Stock Market and Real Estate - Rahman, Sisili; Das, Biplab; Farah, Tazrina (International Journal of Economics and Financial Issues, 2018)
This paper seeks to identify the spillover effect of remittance and private sector credit disbursement, on the capital market and real estate of Bangladesh during the period of 2003-2013. The paper applied Vector Auto regression and Cholesky Factorization to construct spillover index through covariance matrix. The remittance and private sector credit were taken as input variables where market capitalization and real estate sector contribution to GDP were taken as outputs. The model tried to identify asset bubbles using calculated index scores. Both of the asset classes showed getting similar degree of influence by the inputs as their Return spillovers were around 40% and volatility spillovers were around 25%. The score for capital market indicated a bubble and the subsequent crash of 2010-11. As similar scenario was seen in case of real estate, it suggests that real estate too was experiencing a bubble which might lead to a crash soon. Keywords: Asset Bubble, Spillover Index, Vector Auto Regression, Stock Market, Real Estate JEL Classifications: G1, G15, G17, G29 DOI: https://doi.org/10.32479/ijefi.7037